Effects of Transgenic cry1Ca Rice on the Development of Xenopus laevis. - Xiuping Chen; Jiamei Wang; Haojun Zhu; Yunhe Li; Jiatong Ding; Yufa Peng (PLoS ONE)
In fields of genetically modified, insect-resistant rice expressing Bacillus thuringiensis (Bt) proteins, frogs are exposed to Bt Cry proteins by consuming both target and non-target insects, and through their highly permeable skin. In the present study, we assessed the potential risk posed by transgenic cry1Ca rice (T1C-19) on the development of a frog species by adding purified Cry1Ca protein or T1C-19 rice straw into the rearing water of Xenopus laevis tadpoles, and by feeding X. laevis froglets diets containing rice grains of T1C-19 or its non-transformed counterpart MH63. Our results showed that there were no significant differences among groups receiving 100 μg L-1 or 10 μg L-1 Cry1Ca and the blank control in terms of time to completed metamorphosis, survival rate, body weight, body length, organ weight and liver enzyme activity after being exposed to the Cry1Ca (P > 0.05). Although some detection indices in the rice straw groups were significantly different from those of the blank control group (P < 0.05), there was no significant difference between the T1C-19 and MH63 rice straw groups. Moreover, there were no significant differences in the mortality rate, body weight, daily weight gain, liver and fat body weight of the froglets between the T1C-19 and MH63 dietary groups after 90 days, and there were no abnormal pathological changes in the stomach, intestines, livers, spleens and gonads. Thus, we conclude that the planting of transgenic cry1Ca rice will not adversely affect frog development.